Ser Professor de Educação Física: O primeiro contacto com a realidade - Fábio Freitas Miranda (2020)
This report presents the first contact of being a professor of physical education, during the professional internship in a Portuguese school. The internship is, without a doubt, the most important step in the formation of the professor, because it allows the future teacher to contact with the reality that is going to be a part of his life for many years. Thus, the report is narrated by me, the future professor, since the beginning of the formation until the actual practice in a school environment. This report is divided into parts, them being the introduction and conclusion and future perspectives, the starting point and ending point, respectively. The personal and institutional framework is divided into two parts. The first one talks about the personal side and the formation that is acquired by the intern and the second one sends us to the characterization of the context where the internship happened. Lastly, the realization of the professional practice, that ends up being the most important part of this report, is where all the experiences lived in the school environment, the planification, the evaluation, the class management, the difficulties and the problems, as well as the achievements are narrated. Basically, everything that is a part of the learning process. In conclusion, this report is a reflection based on the personal experience that was the first contact with the reality in this last step of formation to become a physical education teacher.